Studi Analisis Finansial Pendirian Industri Keripik Pisang di Provinsi Lampung - Sri Hidayati; Neti Yuliana; Tanto Pratondo Utomo; Rio Cakaradinata (Jurnal Penelitian Pertanian Terapan, 2020)
This study aims to determine the analysis of the location of the establishment of a suitable banana chips industry in Lampung by using an exponential comparison method and the feasibility of financial analysis.. The research method uses observation, survey and interview techniques. To determine the location of the plant using the Exponential Comparison Method. The results showed that the suitable location was Ketapang sub-district in south Lampung regency with a value of 11129 and was declared financially feasible because it had a positive Net Present Value (NPV), the value of the Internal Rate of Return (IRR) was greater than the prevailing interest rate at present, the value of the Benefit/Cost (B/C) ratio is more than 1 and the payback period (payback period 1 year 11 months) is the maximum business feasibility at a 15% increase in raw materials per year.